Performance Analysis of PV/T Modules in West African Climate Zones - TOSSA, Kossoun Alain; nounangn, Cossi Télesphore; Aza-Gnandji, Maurel Richy; SEMASSOU, GUY CLARENCE (My University, 2023)
The use of solar photovoltaic (PV) panels has been seen as a viable solution to improve the rate of rural electricity supply in African states. Today, the use of solar PV systems has helped to overcome low electricity coverage rates. One of the bottlenecks of PV installations in sub-Saharan Africa is the low efficiency of solar PV modules caused largely by heat accumulation during system operation. This research work aims at studying the electrical performances of PV and PVT modules, in the different climatic zones of West Africa, in order to characterize and promote them in rural sanitary areas for the simultaneous production of hot water and electricity. The meteorological data used are of TMY type and come from the PVGIS site. The simulation of the operation of the different PV module technologies implemented in the Simulink/Simscape environment of MATLAB R2021a allowed to estimate the LCOE values, over a typical year, with the different meteorological data of the studied climatic zones. The results obtained show that PVT modules offer LCOE gains ranging from 2% to 12% compared to conventional PV modules. The highest performances are obtained in the Sudanian and Sudan-Sahelian climatic zones, while the Guinean zone shows the lowest gain.
Keywords: PV and PVT modules; weather data; simulation; power generation; LCOE.